POPULASI DAN PERSENTASE SERANGAN HAMA KEPINDING TANAH (Scotinophara coarctata Fabricus.) PADA TANAMAN PADI SAWAH (Oryza sativa L.) DI KECAMATAN KAKAS KABUPATEN MINAHASA - Andrea Wangko; Dantje Tarore; Jusuf Manueke (COCOS, 2018)
ABSTRACT This study aims to determine the population and percentage of S. coarctata attacks on rice plants in Kakas Subdistrict, Minahasa Regency. This research is expected to provide information about the level of damage caused by attacks and pest populations of S. coarctata so that farmers can control soil-borne pests in Kakas District Minahasa Regency. This research uses observational research (survey) conducted in Kakas Subdistrict in two villages (Tontimomor and Kalawiran). From each village as a location of observation, three observation plots were determined. Light traps use modern white electric car lights, which are spread diagonally, the trapping is adjusted to the battery life of 8 hours, the installation is done at 10 pm and the observation is done at 6 am, the sampling is 4 repetitions, with intervals 1 week time for rice plants aged 22-68 days after planting. In Kalawiran village there is 8,5 tails and Tontimomor village, there is 7,6 tails, and then the population of Black Bug lowest observed on IV, in Kalawiran village 3.1 tails and Tontimomor village is 2,3 tails. Based on data analysis, at first, second, third, fourth observation, highest attack on second observed in 38 days after planting, in Kalawiran village 23,79% and Tontimomor village 12,54%. Keywords: population, percentage, S. coarctata